Analysis of The Effect of Marketing Strategy and Digital Marketing on Purchasing Decisions at the Home Industry of Kalamansi Orange’s in The City of Bengkulu - Reza Irawan; Eti Arini (Penerbit Jurnal Indonesia, 2023)
This studi aims to determine analysis of the effect of marketing strategy and digital marketing on purchasing decision at the home industry of kalamansi orange’s in the city of Bengkulu, either partially or simultan. There are several factors that will be discussed in this research, including marketing strategy and Digital Marketing. The object of this research is the consumer of the kalamansi orange’s, which amounts to 70 people. In this research the authors use the method of data collection by means of observation, documentation and distributing questionnaires. Data analysis techniques used in this study, using instrument test, classical assumption test, respondent response analysis, hypothesis testing and determinant coefficient.The results showed that Marketing Strategy has a positive and significant effect on Increasing sales , then the digital marketing shows a positive and significant effect on increasing sales at the home industry of kalamansi orange’s in the city of Bengkulu . So, from the results of the research that has been done, it can be concluded that marketing strategy and digital marketing have a partial or silmutaneous effect on increasing sales at the home industry of kalamansi orange’s in the city of Bengkulu.